Entrepreneurs in Private Higher Education: a Case Study of Education Entrepreneurs in a Middle Income Economy - Yeoh, Seng P. (Emerald Group Publishing, 2014)
This chapter relies on comparative case analysis to examine how and why particular social entrepreneurs in a higher Asian middle income economy broke new grounds in private higher education. The study provides arguments as to why these private higher education entrepreneurs, when viewed inclusively, are social entrepreneurs. Findings from the study suggest that social entrepreneurs distinctively used prior insights from their working experiences to harness the financial power of local capital to fund the scaling up of their social ventures while simultaneously engaging with the country’s economic and social challenges.